Improved dielectric properties of PVDF nanocomposites with core–shell structured BaTiO3 @polyurethane nanoparticles. Issue 3 (1st September 2020) - Zheng, Ming‐Sheng; Zhang, Chong; Yang, Yu; Xing, Zhao‐Liang; Chen, Xin; Zhong, Shao‐Long; Dang, Zhi‐Min
Abstract : Polymer nanocomposites with improved dielectric permittivity and high breakdown strength are extremely desirable for the flexible electronic devices and power systems. The compatibility of fillers and polymer matrix is important in determining the dielectric and breakdown strength properties. The core–shell structure concept is useful to improve the compatibility of fillers with polymer matrix. Herein, an organic thermoplastic urethanes (TPU) polymer shell was successfully grafted on the surface of barium titanate (BaTiO3, BT) and such a TPU shell improved the permittivity and breakdown strength of TPU@BT/PVDF polymer nanocomposites greatly. The permittivity of TPU@BT/PVDF nanocomposites with 12 wt% fillers at 10 2 Hz was up to 13.5, which was 1.5 times higher than that of pure poly(vinylidene fluoride) (PVDF). The improvement of the dielectric properties could be attributed to the enhanced interfacial polarisation between BT nanoparticles and TPU shell. Besides, the compatibility of BT nanoparticles and PVDF matrix was improved after the introduction of TPU shell. Accordingly, a highest breakdown strength value about 373 MV/m was obtained for the TPU@BT/PVDF nanocomposites with 7 wt% fillers. The core–shell strategy could be extended to a variety of inorganic fillers to improve the dielectric and breakdown strength properties of polymer nanocomposites.